IMPLEMENTASI PENETRATION TESTING PADA SISTEM INFORMASI TRIBRATA POLRES PIDIE MENGGUNAKAN METODE OWASP - Narezki, Fujatullah; Yusian TB, Desita Ria (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2025)
AbstractOne factor that must be taken into account is information system security, which is comprised of three components confidentiality, integrity, and availability. One area that requires attention is information system security. Since there are three components to information security—confidentiality, integrity, and availability—an information system must be assessed through penetration testing in order to preserve information security. Enhancing the site's information security is the goal of this penetration test. The Pidie Police Tribrata is a system created in this regard by the Pidie Police, the Aceh Regional Police's readiness unit situated in the Pidie Regency information region. However, penetration testing must be done on the Web application in order to assess the information system's security for the site's security. The Open Web Applications Security Project (OWASP) approach is used for penetration testing on the Pidie Police Tribrata information system. From the results of the penetration testing, several vulnerabilities in the web application were found and these were used as reports to improve the security system in the information system.Keywords: Penetration Testing, OWASP, Information Systems. AbstrakKeamanan sistem informasi merupakan aspek yang perlu diperhatikan. Keamanan informasi terdiri dari 3 aspek yaitu Kerahasiaan, Integritas, Ketersediaan maka dari itu untuk menjaga keamanan informasi tersebut perlu dilakukannya evaluasi dari suatu sistem informasi berupa pengujian penetrasi. Pengujian penetrasi ini bertujuan untuk meningkatkan keamanan sitem informasi. Barkaitan dengan hal tersebut polres pidie yang merupakan satuan Kepolisian Polda Aceh yang berada di wilayah Kabupaten Pidie telah merancang sebuah sistem informasi yakni Tribrata Polres Pidie . Namun keamanan dari Sistem Informasi tersebut perlu diuji untuk mengevaluasi sistem keamananya, maka dari itu perlu dilakukan pengujian penetrasi pada Aplikasi Web tersebut. Pengujian penetrasi pada sistem informasi tribrata Polres Pidie ini menggunakan metode Open Web Aplications SeScurity Project (OWASP). Dari hasil pengujian penetrasi tersebut berhasil ditemukannya beberapa kerentanan pada aplikasi web tersebut dan dijadikan pelaporan untuk meningkatkan sistem keamanan pada sistem informasi tersebut.Kata Kunci: Pegujian Penetrasi, OWASP, Sistem Informasi.